9‐month results of polymer‐free sirolimus eluting stents in young patients compared to a septuagenarian and octogenarian all‐comer population. (4th December 2017) - Kherad, Behrouz; Waliszewski, Matthias; Leschke, Matthias; Kader, Muhammad Ali; Bang, Liew Houng; Ruiz‐Poveda, Fernando Lozano; Pieske, Burkert; Krackhardt, Florian
Abstract : Objectives: To evaluate the 9‐month safety and efficacy of polymer‐free sirolimus eluting drug eluting stents in septuagenarians and octogenarians. Methods: An all‐comer, worldwide single armed trial (ClinicalTrials.gov Identifier NCT02629575) was conducted to demonstrate the safety and efficacy of an ultra‐thin strut, polymer‐free sirolimus eluting stent (PF‐SES). The primary endpoint was the 9‐month target revascularization rate (TLR). Secondary endpoints included the rates of major adverse cardiac events (MACE), stent thrombosis (ST) and bleeding (BARC) in septuagenarians (≥70 years, <80 years), and in octogenarians (≥80 years) to be compared to the younger patient group (<70 years). Results: A total of 1607 patients were treated with PF‐SES in the sub‐70‐year‐old age group, 694 in septuagenarians, and 371 in the octogenarian patient group. At 9 months, the MACE rates were 7.2% in octogenarians, 5.3% in septuagenarians, and 3.0% in the younger patient group ( P  = 0.001). These were mostly driven by all‐cause mortality (4.4% vs 1.9% vs 0.6%, P  < 0.001) while the TLR rates were only numerically lower in the younger age group ( P  = 0.080). BARC 1‐5 bleeding events were more frequent in the older age group (1.9% vs 2.7% vs 4.6%, P  = 0.012) whereas the rates for ST were not different (0.7% vs 0.6% vs 0.6%, P  = 0.970). Conclusions: In octogenarians treated with PF‐SES, the rates for MACE, overall mortality, and bleeding are higher as compared to the younger age groups. However, the rates for TLR and ST were not significantly different across the investigated age groups. PF‐SES are safe and effective in octogenarians.